(N)one of us? The case for descriptive representation of the contemporary working class. Issue 6 (19th September 2022) - Elsässer, Lea; Schäfer, Armin
Abstract: This article departs from the normative-theoretical literature on descriptive representation, which argues that some disadvantaged groups need a special form of representation. Most proponents of a guaranteed presence of women or ethnic minorities, however, do not believe that their arguments equally apply to social classes. The main reason is that the class cleavage historically structured many party systems, making 'class issues' extraordinarily present. However, party systems and industrial relations have vastly changed since then, altering the circumstances under which representation takes place. Evaluating the theoretical arguments for descriptive representation with the help of empirical insights on growing political marginalisation of lower-status classes, this article argues that the societal and political changes of the last decades justify descriptive representation of the contemporary working class.